Mending broken hearts: the future of drug-based cardiac regeneration. (September 2007) - Keating, Mark
Coronary heart disease is a massive health problem worldwide. In the USA alone, 1.2 million people suffer a coronary attack every year, and approximately 40% of these individuals die as a result. As damaged cardiac muscle forms scar tissue and is unable to function properly, those that do survive the attack are often left severely ill. Consequently, the potential for a therapy that allows healthy cardiac muscle to proliferate at the site of injury is enormous. Dr Mark Keating is a leading researcher in this area of regenerative medicine and his group has recently identified a compound that aids in the process of cardiac regeneration. Although currently focussing on ophthalmic drug research at Novartis, Dr Keating still has a great interest in this area. Here he discusses the potential of drug-based cardiac regeneration and the problems that must be overcome before this treatment can reach the clinic.